COMPARISON OF SPEECH FORMS IN UZBEK AND ENGLISH NOVELS - Tulyaganova Nargiza Farxod qizi; Yusupova Shoira Batirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In our article we are going to analyze two well -known novels. It is clear to all of us that writing a book in a detective field is a bit difficult. The reason is that the work should not be only attractive for readers, but also have to be a logical connection in the work.